Analisis Perbandingan Algoritma SHA-256 dan Keccak-256 dalam Smart Contract EVM - Ida Bagus Rizky Brahmantya; Gst. Ayu Vida Mastrika Giri (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
The advancement of blockchain technology has increased the demand for efficient and secure hash algorithms, particularly in the development of smart contracts. This study uses smart contracts on the Ethereum network with inputs of 32, 128, and 1024 characters to evaluate SHA-256 and Keccak-256 based on execution cost, gas fees, and security. According to the results, Keccak-256 is more effective for smart contract computations because it consistently has lower execution costs for all input sizes. Both algorithms perform similarly for big inputs (1024 characters), suggesting comparable storage efficiency at scale, even if its gas charge is marginally greater than SHA-256 for tiny inputs (32 and 128 characters). Keccak-256 and SHA-256 both have strong defenses against brute-force assaults. Both provide similar security, while Keccak-256 takes a little longer to calculate. All things considered, Keccak-256 offers better efficiency, which qualifies it for widespread smart contract implementation. Further research is recommended to explore performance in more complex blockchain environments and execution gas and to optimize gas  for practical implementation.